2017
DOI: 10.1080/14686996.2017.1386531
|View full text |Cite
|
Sign up to set email alerts
|

Membrane thinning for efficient CO2 capture

Abstract: Enhancing the fluxes in gas separation membranes is required for utilizing the membranes on a mass scale for CO2 capture. Membrane thinning is one of the most promising approaches to achieve high fluxes. In addition, sophisticated molecular transport across membranes can boost gas separation performance. In this review, we attempt to summarize the current state of CO2 separation membranes, especially from the viewpoint of thinning the selective layers and the membrane itself. The gas permeation behavior of mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…Ghorbanpour et al [20] have also shown that MOF crystals can be oriented post-synthesis through a solution shearing technique to form highly ordered thin films. These are highly desirable qualities for gas separation membranes, as oriented thin films, along with controlled crystal aspect ratios, allow for a higher flux than packed beds while retaining performance [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ghorbanpour et al [20] have also shown that MOF crystals can be oriented post-synthesis through a solution shearing technique to form highly ordered thin films. These are highly desirable qualities for gas separation membranes, as oriented thin films, along with controlled crystal aspect ratios, allow for a higher flux than packed beds while retaining performance [21].…”
Section: Introductionmentioning
confidence: 99%
“…One way of increasing gas flux is decreasing the thickness of the membrane becauseb oth parameters are inversely proportional.T herefore, ultrathin porous films with thicknesses below 100 nm have the potentialt oe nhance membrane performance by increasingt he flux of gas through the membrane withoutl osing CO 2 selectivity. [5,6] Langmuir-Blodgett (LB) is at echnique especially suitable for this purpose as it enables the self-assembly of aw ide range of molecules/ nanocrystals into dense monolayers. [7] The subsequent transfer of such films to permeable supports opens the possibility to fabricate multilayer membranes with precise control on the thickness of the selective layer.…”
mentioning
confidence: 99%
“…The dual-chamber gas sorption cell was similar to that reported in Koros et al 34 Before measurements, 0.7 g of the sample was weighed and dried at 70 C (343.15 K) for 1 h. CO 2 sorption experiments were carried out at 45 C (318.15 K) and 4 bars. The CO 2 sorption capacity was calculated using eqn (1) and 2:…”
Section: Characterizationmentioning
confidence: 99%
“…In recent times, large-scale emission of CO 2 into the atmosphere triggered by fossil-fuel utilization is considered a critical source for climatic changes and global warming. 1 As a record, since 1958, the atmospheric CO 2 concentration dominantly increased every year with the latest highest recorded value of 414 ppm (https://www.esrl.noaa.gov/gmd/ccgg/trends/). The rise in CO 2 level in the atmosphere is predicted to reach a value of 450 ppm in 2100, with an increase of more than 2 C of the global temperature, due to continuing industrial revolution.…”
Section: Introductionmentioning
confidence: 99%